Just kids [compact disc, unabridged] - Smith, Patti (Harper Audio, 2011)
In the summer when Coltrane died, poet Patti Smith fell in love with photographer Robert Mapplethorpe. Eventually the two joined up with the Andy Warhol superstars and called Hotel Chelsea home. Here Smith recounts her passionate romance and the incredible artistic atmosphere of the 1960s in this National Book Award-winning biography.